Appraisals - Pollan, Michael (World Nutrition, 2013)
Second month. Forward to nature. The impact of his writing on US and other food systems Simon Schama, Todd Dawson, Alice Waters, Christopher Gardner Boyd Swinburn, Francine Lima, Isabela Sattamini Critical views: Benjamin Caballero, Michael Gibney, Adam Merberg. Plus Michael Pollan on his favourite new books